2010
DOI: 10.3109/14992020903092608
|View full text |Cite
|
Sign up to set email alerts
|

AMTAS®: Automated method for testing auditory sensitivity: Validation studies

Abstract: Three studies are reported assessing the validity of AMTAS, an automated method for obtaining an audiogram, including air- and bone-conduction thresholds (stimuli delivered by a forehead-placed transducer) with masking noise presented to the non-test ear. In Study 1, six subjects at each of three sites were tested using manual audiometry by two audiologists at each site. The mean differences between the audiograms for the paired audiologists provided a measure of the reliability of traditional audiometry. In S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
151
6
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(178 citation statements)
references
References 10 publications
13
151
6
4
Order By: Relevance
“…Air-conduction thresholds measured in the natural and standard audiometric booth corresponded within typical 5dB or less test-retest limits for thresholds measured in a sound booth (Stuart et al 1991;Smith-Olinde et al 2006;Margolis et al 2010;Swanepoel, Mngemane et al 2010;Swanepoel & Biagio, 2011). Average absolute air-conduction threshold differences for the current study (2.7 ± 3.1 dB) were within previously reported average test-retest absolute difference values (3.6 ± 3.9 dB and 3.5 ± 3.8 dB) for the same audiometer (Swanepoel, Mngemane et al 2010;Swanepoel & Biagio, 2011).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Air-conduction thresholds measured in the natural and standard audiometric booth corresponded within typical 5dB or less test-retest limits for thresholds measured in a sound booth (Stuart et al 1991;Smith-Olinde et al 2006;Margolis et al 2010;Swanepoel, Mngemane et al 2010;Swanepoel & Biagio, 2011). Average absolute air-conduction threshold differences for the current study (2.7 ± 3.1 dB) were within previously reported average test-retest absolute difference values (3.6 ± 3.9 dB and 3.5 ± 3.8 dB) for the same audiometer (Swanepoel, Mngemane et al 2010;Swanepoel & Biagio, 2011).…”
Section: Discussionsupporting
confidence: 67%
“…The average absolute difference in bone-conduction thresholds recorded in the natural and audiometric booth (3.4 ± 4.3 dB) was within previously reported bone-conduction test-retest differences (Laukli & Fjermedal, 1990;Margolis et al 2010;Swanepoel & Biagio, 2011). The average absolute test-retest variability for this same audiometer previously reported in a small group of 10 normal-hearing subjects was 7.1 ± 6.4 dB.…”
Section: Discussionsupporting
confidence: 63%
“…Whilst previous studies have excluded participants as outliers (Storey et al, 2014), the outliers in the present study were specific to thresholds, not individuals themselves. Inter and intra-tester variability scores were not possible to assess in this study, but previous studies have indicated that the average level of inter-tester variation can be between 2.3-6.0 dB for air-conduction thresholds and 2.9-7.9 dB for bone-conduction thresholds (Margolis et al, 2010). This does not include clinician-specific variation around certain frequencies such as 4000 Hz (Margolis et al, 2013), which may also have increased variation in the results.…”
Section: Accuracymentioning
confidence: 97%
“…The ability to provide automated audiometric testing in the absence of a sound-treated environment has a great potential to increase service provision to low and middle-income countries, and rural and remote areas of high-income countries that do not have these facilities. At least two of the contemporary clinically available automation-capable audiometers use audiocups to provide attenuation from environmental sounds (Margolis et al, 2010;Swanepoel & Biagio, 2011), and studies have demonstrated their potential feasibility in environments that are not soundtreated Maclennan-Smith et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation